A Theory on the Future of the Rebound Effect in a Resource-Constrained World - Freeman, Rachel (Frontiers in Energy Research, 2018)
The paradox underlying the rebound effect is that, due to secondary effects, improvements in resource efficiency provide smaller reductions in the consumption of energy and/or material resources than are expected – or even an overall net increase in resource use. The rebound effect has played a part in economic growth and industrialisation, yet it remains a problem for the task of reducing negative environmental impacts. This paper proposes that the size of the rebound effect, and the type of impacts it causes, may be affected by future changes in the system within which it arises. Four types of rebound effect are considered: economy-wide effects, transformational effects, frontier effects, and international rebound effects. A conceptual model of the historical role of the rebound effect in socio-technical systems, and the relationship of socio-technical systems with the environment in which they exist, provides a “sandbox” for testing ideas about the future. The theory underlying the conceptual model draws upon the concepts of natural capital, the Global Ecological Footprint, and the Great Acceleration. How the size of four types of the rebound effect might change in future, as supplies of resources from natural capital become more constrained, is discussed within three storylines. In the first storyline, natural capital declines but remains fairly stable; rebound is much decreased as resources are less available and efficiency is used up more in stabilising supplies of goods and services. In the second storyline, growth continues without constraint amid regional rivalry; eventually there is a strong downturn in availability of resources and negative impacts on society and on natural capital. In the third storyline, impact caps are implemented for different types of resources; for some time, industry and society adapt by investing in low resource use innovation and global cooperation on management of natural capital; once natural capital recovers and stabilises, growth and consumption may increase along with rebound but staying within a Global Ecological Footprint of 1 Earth. The theory and model in this paper are intended to contribute to new thinking on the subject of the rebound effect.